Eye-Closure Enhances Creative Performance on Divergent and Convergent Creativity Tasks - Ritter, Simone M.; Abbing, Jens; van Schie, Hein T. (Frontiers in Psychology, 2018)
In today’s world of rapid changes and increasing complexity, understanding and enhancing creativity is of critical importance. Studies investigating EEG correlates of creativity linked power in the alpha frequency band to creativity, and alpha-power has been interpreted as reflecting attention on internal mental representations and inhibition of external sensory input. Thus far, however, there is no direct evidence for the idea that internally directed attention facilitates creativity. The aim of the current study was to experimentally investigate the relationship between eye-closure—a simple and effective means to stimulate internally directed attention—and creativity. Moreover, to test whether the potential beneficial effect of eye-closure is specific for creativity, or whether it improves general cognitive functioning, the current study tested the effect of eye-closure on creativity and on working memory. Participants completed four tasks to measure divergent and convergent creativity (Adapted Alternative Uses Test, Remote Associates Test, Sentence Construction Test, Word Construction Test), and one task to measure working memory (Digit Span Test). For each task, participants had to perform two versions, one version with eyes open and one version with eyes closed. Eye-closure facilitated creative performance on the classical divergent and convergent creativity tasks (Adapted Alternative Uses Test, Remote Associates Test). No effect of eye-closure was observed on the working memory task. These findings provide empirical support for the hypothesis that creativity relies on internally directed attention and provide a novel and easily applicable means to enhance divergent and convergent creativity through eye-closure.